The Smoke Temperature Analysis and Smoke Gas Component Distribution Using the Staircase Pressurisation System - Rusli, Muhammad Asyraf; Ahmad Kamal, Ahmad Syazwan; Tarmizi, Mohd Redzuan; Anwat Khan, Muhammad Firdaus Khan; Kamal, Hasrul; Ismail, Mohd Azmi (Applications of Modelling and Simulation, 2025)
This study investigates the impact of staircase pressurisation systems on smoke temperature and the distribution of smoke gas components in a 3-storey building using Computational Fluid Dynamics (CFD) simulations. Staircase pressurisation systems are designed to create a differential pressure that prevents smoke infiltration, ensuring staircases remain safe evacuation routes. This research uses CFD to predict the effectiveness of pressurised staircase systems on smoke gas product carbon dioxide (CO2) infiltration into the staircase space at a differential pressure of 50 Pa, as per MS 1472, in comparison to a non-pressurised staircase system. The inlet of the smoke mass flow rate and temperature are 6.544 kg/s and 535K, respectively. The simulations reveal that without a pressurisation system, smoke can occupy the 3-storey building in less than 5 minutes. Conversely, the pressurisation system prevents smoke from propagating and infiltrating the stairwell. Moreover, the staircase pressurisation system reduces the maximum air temperature in the staircase space from 535K to approximately 307K. This study analyses both smoke temperature and gas component distribution to evaluate the effectiveness of staircase pressurisation systems.